Composite polymer solid electrolyte, solid-state battery and preparation method thereof

By using composite polymer solid electrolytes in solid lithium batteries, the copolymerization of fluoroacrylate monomer and unsaturated cyanophenyl acrylic acid monomer is used to form an electrolyte with high ionic conductivity and flexible interface, which solves the problem of decomposition of solid lithium batteries at high voltages and significantly improves the cycling and safety performance of the battery.

CN119742441APending Publication Date: 2025-04-01SICHUAN CHANGHONG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411940302.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The circulation and safety performance of existing solid-state lithium batteries are poor, especially at high voltages, and the decomposition of the positive electrode and electrolyte is serious, affecting the battery life and safety.

Method used

Using a composite polymer solid electrolyte, including fluoroacrylate monomer, unsaturated cyanophenyl acrylic acid monomer, functional additives, lithium salts and initiators, the electrolyte is formed through in-situ polymerization to enhance the stability and flexibility of the interface.

Benefits of technology

It significantly improves the ionic conductivity, elasticity and oxidation stability of the electrolyte, inhibits the expansion of the silicon-based negative electrode, improves the cycle performance and safety performance of the battery, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212439380000101
    Figure BDA0005212439380000101
Patent Text Reader

Abstract

The present invention discloses a composite polymer solid electrolyte, a solid-state battery and a preparation method thereof. The composite polymer solid electrolyte comprises a fluoroacrylate monomer, an unsaturated cyanophenyl acrylic acid monomer, a functional additive, a lithium salt and an initiator. In the present invention, a cyanophenyl group and a fluorine-containing group are introduced into the composite polymer solid electrolyte by in-situ polymerization, and the cyanophenyl group has a strong complexation with the transition metal in the positive electrode to inhibit the dissolution of the transition metal, thereby ensuring the stability of the positive electrode particle structure, enhancing the interface stability and extending its life. At the same time, the flexibility of the skeleton where the cyanophenyl group is located is utilized to enhance the flexibility of the interface; in addition, the fluorine-containing group can also promote the formation of the electrode fluorine-containing interface layer, further extending the life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a composite polymer solid electrolyte, a solid-state battery and a preparation method thereof. Background Art

[0002] With the continuous development of new energy vehicles, the energy density of the mainstream on-board lithium iron phosphate batteries in the market is less than 200Wh / kg, which is difficult to meet the mileage requirements of consumers. Therefore, a positive and negative electrode system with higher energy density is needed to gradually replace lithium iron phosphate batteries. Among them, the high-nickel ternary positive electrode-silicon-based negative electrode system is one of the battery systems with the most market potential. In terms of positive electrode, high-nickel ternary positive electrode materials have received widespread attention due to their wider operating voltage range (2.5~4.3V) and higher theoretical specific capacity (200-220mAh g-1); in terms of negative electrode, silicon-based negative electrode is considered to be a strong competitor for the next generation of lithium-ion battery negative electrode materials due to its ultra-high theoretical specific capacity (>600mAh g-1), lower lithium insertion potential (<0.4V) and wide source and environmental friendliness. However, the wider operating voltage range and unstable positive and negative electrode materials affect the cycle performance and safety performance of the battery of this system. Moreover, current commercial lithium-ion batteries usually use organic liquid electrolytes, which have disadvantages such as electrolyte leakage, flammability and explosion, and lithium dendrites penetrating the diaphragm. Therefore, it is very necessary to use non-flammable electrolytes.

[0003] Based on this, replacing organic liquid electrolytes with composite polymer solid electrolytes is considered to be the best way to solve the safety problem of lithium-ion batteries. At present, the composite polymer solid electrolyte systems that are studied more include inorganic composite polymer solid electrolytes represented by oxides and sulfides, and composite polymer solid electrolytes represented by PEO. Among them, solid polymer electrolytes (SPEs) are particularly attractive due to their processability, light weight, low cost and flexibility. The in-situ polymerized and cured polymer electrolytes inherit the advantages of good interface contact between liquid electrolytes and electrodes, which is conducive to improving the cycle performance of batteries. Their manufacturing process is compatible with the existing lithium-ion battery manufacturing process and is easy to achieve large-scale production. It is one of the most concerned process routes for manufacturing high-energy-density solid-state lithium-ion batteries. However, they have low oxidation stability and are prone to form thick and uneven electrode / electrolyte interface layers, which hinder the transmission of Li+ and increase the impedance of the entire battery, limiting their use with high-voltage, high-nickel (Ni) positive electrodes (such as LiNi0.8Co0.1Mn0.1O2, NCM811), which poses a challenge in the development of high-energy-density LMBs.

[0004] In addition, there are a lot of studies on improving the oxidation stability of polymer electrolytes and their interfacial phases, mainly in the following aspects: designing double-layer electrolytes, coating high-nickel cathode materials, adding inorganic particles to polymers, etc. However, the design of double-layer electrolytes and coating cathode materials are complex, and the dispersion uniformity of inorganic particles added to polymers is poor, and the composite effect is not ideal.

[0005] Therefore, a solid-state lithium battery with high energy density and high safety performance needs to be developed urgently. Summary of the invention

[0006] In order to solve the problems of poor cyclability and safety of existing solid-state batteries, one of the objectives of the present invention is to provide a composite polymer solid electrolyte.

[0007] The technical solution of the present invention to solve the above technical problems is as follows: a composite polymer solid electrolyte comprises a fluoroacrylate monomer, an unsaturated cyanophenyl acrylic acid monomer, a functional additive, a lithium salt and an initiator.

[0008] The beneficial effects of the present invention are as follows: in the present invention, the cyanophenyl group has a strong complexation with the transition metal in the positive electrode, which can inhibit the dissolution of the transition metal, thereby ensuring the stability of the positive electrode particle structure, helping to inhibit the decomposition of the electrolyte and the positive electrode at high voltage, enhancing the stability of the interface, and extending the life of the battery.

[0009] On the basis of the above technical solution, the present invention can also be improved as follows:

[0010] Furthermore, the molar ratio of the fluoroacrylate monomer to the unsaturated cyanophenyl acrylic acid monomer is 4:1 to 4:6.

[0011] The beneficial effect of adopting the above further technical solution is that the composite polymer solid electrolyte within the molar ratio has good structural elasticity, effectively inhibits the expansion of the silicon-based negative electrode, and avoids the excessive amount of unsaturated cyanophenyl acrylic acid monomer causing the polymer chain in the composite polymer solid electrolyte to be destroyed, thereby reducing the interface stability and deteriorating the cycle performance of the solid-state battery. Further preferably, the molar ratio of the fluoroacrylate monomer to the unsaturated cyanophenyl acrylic acid monomer in the present invention is 4:2.

[0012] Further, the fluoroacrylate monomer is at least one of 2-fluoroethyl acrylate, perfluoroalkyl acrylate, perfluoropolyether (meth) acrylate, perfluorooctylpropyl acrylate, trifluoroethyl acrylate and perfluoroalkylethyl acrylate;

[0013] The unsaturated cyanophenyl acrylic acid monomer is at least one of ethyl 2-(4-cyanophenyl)acrylate, 3-(2-cyanophenyl)acrylic acid, tert-butyl 3-(4-cyanophenyl)acrylate, methyl 3-(3-benzonitrile)acrylate and ethyl 4-cyanocinnamate.

[0014] The beneficial effect of adopting the above-mentioned further technical scheme is that the skeleton where the cyanophenyl group is located in the present invention is flexible, and the electron-withdrawing fluorine-containing group can promote the formation of the electrode fluorine-containing interface layer to form an organic-inorganic composite SEI; therefore, the flexible electrolyte and composite SEI in the present invention can inhibit the volume expansion of the silicon-based negative electrode and have a very high coulombic efficiency, while enhancing the flexibility of the interface and extending the life of the battery.

[0015] Further, the ratio of the mass of the functional additive to the mass of the fluoroacrylate monomer and the unsaturated cyanophenyl acrylic acid monomer is 10:1 to 25:1;

[0016] The molar concentration of the lithium salt in the mixture of the fluoroacrylate monomer, the unsaturated cyanophenyl acrylic acid monomer and the functional additive is 0.8 to 2 mol / L;

[0017] The mass of the initiator is 0.2-5 wt % of the total mass of the fluorinated acrylate monomer and the unsaturated cyanophenyl acrylic acid monomer.

[0018] Further, the functional additive is at least one of vinylene carbonate, fluoroethylene carbonate, vinyl carbonate, (trimethylsilyl) phosphite, tris(trimethylsilyl) borate, 1,3-propane sultone, vinyl sulfate, methylene methanedisulfonate, succinonitrile, adiponitrile, ethylene glycol dimethyl ether and dimethyl carbonate;

[0019] The lithium salt is at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium tetrafluoroborate;

[0020] The initiator is at least one of azobisisobutyronitrile, dibenzamide peroxide, benzoyl peroxyacetic acid and dibutyl peroxybenzoylformate.

[0021] A second aspect of the present invention provides a solid-state battery, comprising a positive electrode, a negative electrode, a separator and a composite polymer solid electrolyte according to one of the purposes of the present invention, wherein the composite polymer solid electrolyte is in contact with both the positive electrode and the negative electrode.

[0022] Furthermore, the positive electrode is a high-nickel ternary positive electrode, and the negative electrode is a silicon-based negative electrode; preferably, the separator is a polyethylene film or a polypropylene film.

[0023] A third aspect of the present invention provides a method for preparing a solid-state battery, comprising the following steps:

[0024] Step 1, firstly, mixing a fluoroacrylate monomer and an unsaturated cyanophenyl acrylic acid monomer, then adding a functional additive and continuing to mix evenly, then adding a lithium salt and mixing evenly, and finally adding an initiator and mixing evenly to obtain a composite polymer solid electrolyte precursor;

[0025] Step 2: First assemble the positive and negative electrodes and the separator, then inject the composite polymer solid electrolyte precursor, and then sequentially perform standing, pressurizing and thermal curing to obtain a solid-state battery.

[0026] The beneficial effects of the present invention are as follows: through thermal curing, the fluoroacrylate monomer and the unsaturated cyanophenyl acrylic acid monomer in the polymer solid electrolyte precursor are promoted to undergo in-situ polymerization, thereby changing the contact relationship between the polymer solid electrolyte and the positive and negative electrodes, enhancing the stability and flexibility of the interface, and thereby improving the cyclability and safety of the solid-state battery.

[0027] Furthermore, the standing temperature is room temperature and the standing time is 12 to 48 hours; preferably, the standing temperature is 20°C ± 5.

[0028] Further, the temperature of thermal curing is 50 to 90°C and the time is 2 to 12 hours;

[0029] The pressurized pressure is 0.2 to 1 MPa, and the time is 30 to 120 seconds.

[0030] The present invention has the following beneficial effects:

[0031] 1. The composite polymer solid electrolyte in the present invention is formed by in-situ polymerization, and the composite polymer solid electrolyte significantly improves the ionic conductivity, elasticity and oxidative stability of the electrolyte. In the present invention, in-situ polymerization improves the interface contact between the composite polymer solid electrolyte and the positive and negative electrodes, which is conducive to the formation of a stable SEI layer, which can inhibit the volume expansion of the silicon-based negative electrode and has a high coulombic efficiency. At the same time, the CEI formed at the high-nickel positive electrode helps to inhibit the decomposition of the polymer solid electrolyte and the positive electrode at high voltage, effectively improving the cycle performance of the battery; and the wide electrochemical window, leakage-proof, and non-flammable polymer further effectively improves the safety performance of the battery.

[0032] 2. The present invention introduces cyanophenyl groups into the composite polymer solid electrolyte through copolymerization, and simultaneously introduces electron-withdrawing fluorine-containing groups, thereby providing an in-situ polymerized composite polymer solid electrolyte suitable for a high-nickel ternary positive electrode-silicon-based negative electrode system.

[0033] The present invention adds cyano groups to polymers by copolymerization, avoids the problem that the strong reducibility of cyano groups makes it difficult to be used in batteries, and also reduces its reactivity. In addition, when cyano groups are embedded in bulk polymers, the accessibility of their chemical reactions is significantly reduced due to steric hindrance. In addition, the cyanophenyl groups in the unsaturated cyanophenyl acrylic acid monomers of the present invention have a strong complexation with the transition metal in the positive electrode, which can inhibit the dissolution of the transition metal, thereby ensuring the stability of the positive electrode particle structure, and helping to inhibit the decomposition of the electrolyte and the positive electrode at high voltage; and the skeleton where the cyanophenyl groups are located is flexible, and the electron-withdrawing fluorine-containing groups can promote the formation of the electrode fluorine-containing interface layer, forming an organic-inorganic composite SEI, and the flexible electrolyte and the composite SEI can inhibit the volume expansion of the silicon-based negative electrode and have a high coulomb efficiency. This dual effect greatly enhances the interface stability and elasticity, and prolongs the cycle life of the battery.

[0034] Therefore, the composite polymer solid electrolyte in the present invention has a bicontinuous structure, that is, the coexistence of elastomer and plastic crystal phases, which significantly improves the ionic conductivity, elasticity and oxidation stability of the electrolyte. In addition, the in-situ polymerization technology simultaneously improves the interface contact between the composite polymer solid electrolyte and the positive and negative electrodes, effectively improving the cycle performance of the battery. DETAILED DESCRIPTION

[0035] A composite polymer solid electrolyte, a solid-state battery and a preparation method thereof in the present invention will be described below in conjunction with embodiments.

[0036] However, the present invention may be exemplified in many different forms and should not be construed as limited to the specific embodiments set forth herein; rather, these embodiments are provided so that this invention will be thorough and complete and will fully convey the scope of the invention to those skilled in the art.

[0037] Example 1

[0038] Step 1. In a glove box filled with argon (Ar), trifluoroethyl acrylate and ethyl 2-(4-cyanophenyl)acrylate are first mixed in a molar ratio of 4:1 to obtain a first solution; a functional additive fluoroethylene carbonate is added to the first solution, and the mass ratio of fluoroethylene carbonate to the first solution is 25:1; LiTFSI (lithium bistrifluoromethanesulfonyl imide) and LiDFOB (lithium difluorooxalatoborate) are continued to be added, wherein the molar concentration of LiTFSI in the first solution with the functional additive is 0.6 mol / L, and the molar concentration of LiDFOB in the first solution with the functional additive is 0.2 mol / L; and then 0.2 wt% of the mass of the first solution as an initiator azobisisobutyronitrile is added to obtain a composite polymer solid electrolyte precursor solution.

[0039] Step 2: Inject the precursor solution into the dry battery cell assembled with the positive and negative electrode sheets (wherein the positive electrode is a high-nickel ternary positive electrode and the negative electrode is a silicon-based negative electrode) and the diaphragm (the diaphragm is a polyethylene film). After packaging, let it stand at room temperature for 12 hours, then keep it at a pressure of 0.2 MPa for 120 seconds and then put it into a hot oven, and react it at 50°C for 2 hours to obtain an organic composite polymer solid electrolyte, and finally prepare a solid-state battery.

[0040] Step 3: The solid-state battery is further formed, sealed, capacity divided, and aged to complete the production of the soft-pack battery.

[0041] Example 2

[0042] Step 1, in a glove box filled with argon (Ar), firstly, trifluoroethyl acrylate and ethyl 2-(4-cyanophenyl)acrylate are mixed in a molar ratio of 4:2 to obtain a first solution; functional additive fluoroethylene carbonate is added to the first solution, and the mass ratio of fluoroethylene carbonate to the first solution is 25:1; LiTFSI (lithium bistrifluoromethanesulfonyl imide) and LiDFOB (lithium difluorooxalatoborate) are continuously added, wherein the molar concentration of LiTFSI in the first solution with the functional additive is 0.8 mol / L, and the molar concentration of LiDFOB in the first solution with the functional additive is 0.2 mol / L; and then 0.5 wt% of the mass of the first solution as an initiator azobisisobutyronitrile is added to obtain a composite polymer solid electrolyte precursor solution.

[0043] Step 2: Inject the precursor solution into the dry battery cell assembled with positive and negative electrode sheets (wherein the positive electrode is a high-nickel ternary positive electrode and the negative electrode is a silicon-based negative electrode) and a diaphragm (the diaphragm is a polyethylene film). After packaging, let it stand at room temperature for 24 hours, then keep it at a pressure of 0.4 MPa for 30 seconds and then put it into a hot oven to react at 50°C for 12 hours to obtain an organic composite polymer solid electrolyte, and finally prepare a solid-state battery.

[0044] Step 3: The solid-state battery is further formed, sealed, capacity divided, and aged to complete the production of the soft-pack battery.

[0045] Example 3

[0046] Step 1, in a glove box filled with argon (Ar), firstly, trifluoroethyl acrylate and ethyl 2-(4-cyanophenyl)acrylate are mixed in a molar ratio of 4:3 to obtain a first solution; functional additive fluoroethylene carbonate is added to the first solution, and the mass ratio of fluoroethylene carbonate to the first solution is 25:1; LiTFSI (lithium bistrifluoromethanesulfonyl imide) and LiDFOB (lithium difluorooxalatoborate) are continuously added, wherein the molar concentration of LiTFSI in the first solution with the functional additive is 1.6 mol / L, and the molar concentration of LiDFOB in the first solution with the functional additive is 0.4 mol / L; and then 5 wt% of the mass of the first solution as an initiator azobisisobutyronitrile is added to obtain a composite polymer solid electrolyte precursor solution.

[0047] Step 2: Inject the precursor solution into the dry battery cell assembled with positive and negative electrode sheets (wherein the positive electrode is a high-nickel ternary positive electrode and the negative electrode is a silicon-based negative electrode) and a diaphragm (the diaphragm is a polyethylene film). After packaging, let it stand at room temperature for 48 hours, then keep it at a pressure of 1 MPa for 30 seconds and then put it into a hot oven and react at 90°C for 2 hours to obtain an organic composite polymer solid electrolyte, and finally prepare a solid-state battery.

[0048] Step 3: The solid-state battery is further formed, sealed, capacity divided, and aged to complete the production of the soft-pack battery.

[0049] Example 4

[0050] Step 1, in a glove box filled with argon (Ar), firstly, trifluoroethyl acrylate and ethyl 2-(4-cyanophenyl)acrylate are mixed in a molar ratio of 4:6 to obtain a first solution; functional additive fluoroethylene carbonate is added to the first solution, and the mass ratio of fluoroethylene carbonate to the first solution is 25:1; LiTFSI (lithium bistrifluoromethanesulfonyl imide) and LiDFOB (lithium difluorooxalatoborate) are continuously added, wherein the molar concentration of LiTFSI in the first solution with the functional additive is 0.8 mol / L, and the molar concentration of LiDFOB in the first solution with the functional additive is 0.2 mol / L; and then 0.5 wt% of the mass of the first solution as an initiator azobisisobutyronitrile is added to obtain a composite polymer solid electrolyte precursor solution.

[0051] Step 2: Inject the precursor solution into the dry battery cell assembled with positive and negative electrode sheets (wherein the positive electrode is a high-nickel ternary positive electrode and the negative electrode is a silicon-based negative electrode) and a diaphragm (the diaphragm is a polyethylene film). After packaging, let it stand at room temperature for 24 hours, then keep it at a pressure of 0.4 MPa for 30 seconds and then put it into a hot oven and react at 50°C for 12 hours to obtain an organic composite polymer solid electrolyte, and finally prepare a solid-state battery.

[0052] Step 3: The solid-state battery is further formed, sealed, capacity divided, and aged to complete the production of the soft-pack battery.

[0053] Comparative Example 1

[0054] Step 1, in a glove box filled with argon (Ar), add functional additive fluoroethylene carbonate to trifluoroethyl acrylate, the mass ratio of which to trifluoroethyl acrylate is 25:1; continue to add LiTFSI (lithium bistrifluoromethanesulfonyl imide) and LiDFOB (lithium difluorooxalatoborate), wherein the molar concentration of LiTFSI in the first solution with the functional additive is 0.8 mol / L, and the molar concentration of LiDFOB in the first solution with the functional additive is 0.2 mol / L; then add 0.5wt% initiator azobisisobutyronitrile based on the mass of trifluoroethyl acrylate, and finally obtain a composite polymer solid electrolyte precursor solution.

[0055] Step 2: Inject the precursor solution into the dry battery cell assembled with positive and negative electrode sheets (wherein the positive electrode is a high-nickel ternary positive electrode and the negative electrode is a silicon-based negative electrode) and a diaphragm (the diaphragm is a polyethylene film). After packaging, let it stand at room temperature for 24 hours, then keep it at a pressure of 0.4 MPa for 30 seconds and then put it into a hot oven, and react it at 50°C for 12 hours to obtain an organic composite polymer solid electrolyte, and finally prepare a solid-state battery.

[0056] Step 3: The solid-state battery is further formed, sealed, capacity divided, and aged to complete the production of the soft-pack battery.

[0057] Comparative Example 2

[0058] Step 1, in a glove box filled with argon (Ar), adding functional additive fluoroethylene carbonate to ethyl 2-(4-cyanophenyl)acrylate, wherein the mass ratio of fluoroethylene carbonate to ethyl 2-(4-cyanophenyl)acrylate is 25:1; continuing to add LiTFSI (lithium bistrifluoromethanesulfonyl imide) and LiDFOB (lithium difluorooxalatoborate), wherein the molar concentration of LiTFSI in the first solution with the functional additive is 0.8 mol / L, and the molar concentration of LiDFOB in the first solution with the functional additive is 0.2 mol / L; and then adding 0.5 wt% initiator azobisisobutyronitrile based on the mass of ethyl 2-(4-cyanophenyl)acrylate to obtain a composite polymer solid electrolyte precursor solution.

[0059] Step 2: Inject the precursor solution into the dry battery cell assembled with positive and negative electrode sheets (wherein the positive electrode is a high-nickel ternary positive electrode and the negative electrode is a silicon-based negative electrode) and a diaphragm (the diaphragm is a polyethylene film). After packaging, let it stand at room temperature for 24 hours, then keep it at a pressure of 0.4 MPa for 30 seconds and then put it into a hot oven, and react it at 50°C for 12 hours to obtain an organic composite polymer solid electrolyte, and finally prepare a solid-state battery.

[0060] Step 3: The solid-state battery is further formed, sealed, capacity divided, and aged to complete the production of the soft-pack battery.

[0061] Comparative Example 3

[0062] Step 1, in a glove box filled with argon (Ar), firstly, trifluoroethyl acrylate and ethyl 2-(4-cyanophenyl)acrylate are mixed in a molar ratio of 4:7 to obtain a first solution; functional additive fluoroethylene carbonate is added to the first solution, and the mass ratio of fluoroethylene carbonate to the first solution is 25:1; LiTFSI (lithium bistrifluoromethanesulfonyl imide) and LiDFOB (lithium difluorooxalatoborate) are continuously added, wherein the molar concentration of LiTFSI in the first solution with the functional additive is 0.8 mol / L, and the molar concentration of LiDFOB in the first solution with the functional additive is 0.2 mol / L; and then 0.5 wt% of the mass of the first solution as an initiator azobisisobutyronitrile is added to obtain a composite polymer solid electrolyte precursor solution.

[0063] Step 2: Inject the precursor solution into the dry battery cell assembled with positive and negative electrode sheets (wherein the positive electrode is a high-nickel ternary positive electrode and the negative electrode is a silicon-based negative electrode) and a diaphragm (the diaphragm is a polyethylene film). After packaging, let it stand at room temperature for 24 hours, then keep it at a pressure of 0.4 MPa for 30 seconds and then put it into a hot oven and react at 50°C for 12 hours to obtain an organic composite polymer solid electrolyte, and finally prepare a solid-state battery.

[0064] Step 3: The solid-state battery is further formed, sealed, capacity divided, and aged to complete the production of the soft-pack battery.

[0065] Comparative Example 4

[0066] Step 1, in a glove box filled with argon (Ar), firstly, trifluoroethyl acrylate and ethyl cyanoacrylate are mixed in a molar ratio of 4:6 to obtain a first solution; functional additive fluoroethylene carbonate is added to the first solution, and the mass ratio of fluoroethylene carbonate to the first solution is 25:1; LiTFSI (lithium bistrifluoromethanesulfonyl imide) and LiDFOB (lithium difluorooxalatoborate) are continuously added, wherein the molar concentration of LiTFSI in the first solution with the functional additive is 0.8 mol / L, and the molar concentration of LiDFOB in the first solution with the functional additive is 0.2 mol / L; and then 0.5 wt% of the mass of the first solution as an initiator azobisisobutyronitrile is added to obtain a composite polymer solid electrolyte precursor solution.

[0067] Step 2: Inject the precursor solution into the dry battery cell assembled with positive and negative electrode sheets (wherein the positive electrode is a high-nickel ternary positive electrode and the negative electrode is a silicon-based negative electrode) and a diaphragm (the diaphragm is a polyethylene film). After packaging, let it stand at room temperature for 24 hours, then keep it at a pressure of 0.4 MPa for 30 seconds and then put it into a hot oven and react at 50°C for 12 hours to obtain an organic composite polymer solid electrolyte, and finally prepare a solid-state battery.

[0068] Step 3: The solid-state battery is further formed, sealed, capacity divided, and aged to complete the production of the soft-pack battery.

[0069] Test analysis:

[0070] 1. High-voltage stability test: The soft-pack batteries prepared by Examples 1-4 and Comparative Examples 1-4 were subjected to a high-voltage stability test. The test conditions were as follows: a sweep rate of 0.2 mV / s was used, and the linear sweep voltammetric curve was tested from the open circuit voltage to the 6 V cutoff. The test results are detailed in Table 1.

[0071] 2. Electrochemical performance test: The soft-pack batteries assembled using Examples 1-4 and Comparative Examples 1-4 were tested for 1C cycle performance at 3.0-4.7V, and the battery swelling was monitored. The test results are detailed in Table 1.

[0072] Table 1. Test results

[0073]

[0074] It can be seen from Table 1 above that the electrochemical window of Comparative Example 1 is as low as 4.45V, while the electrochemical window value of Comparative Example 2 reaches 5.2V, indicating that the addition of cyanophenyl groups can effectively improve the antioxidant properties of the electrolyte and improve the high voltage resistance of the battery; it can also be seen from Examples 1-4 that as the proportion of cyanophenyl groups added increases, the electrochemical window is further improved.

[0075] In addition, from the analysis of Table 1 above, it can be seen that the initial discharge capacity of the battery of Example 1 is 192.7 mAh / g, and after 100 cycles, the capacity retention rate is 80.2%, and the average coulombic efficiency is 98.6%. In contrast, the initial discharge capacity of the battery of Example 2 is 198.8 mAh / g, and after 100 cycles, the capacity retention rate is 88.6.2%, and the average coulombic efficiency is as high as 99.8%; although the electrolyte of Example 3 has a higher electrochemical window, the initial capacity is 190.5 mAh / g, and the capacity retention after 100 cycles is only 75.4%.

[0076] Furthermore, it can be seen from Examples 1 to 4 and Comparative Example 3 that when the molar ratio of the fluoroacrylate monomer to the unsaturated cyanophenyl acrylic acid monomer exceeds 4:6, the battery capacity and cycle performance are poor. These results indicate that excessive addition of cyanophenyl will destroy the structural elasticity of the polymer chain, affect the interface stability and thus affect the battery's cycle performance.

[0077] In addition, it can be seen from Table 1 that Example 2 has better coulombic efficiency and cycle performance. These results show that in different electrolytes, the molar ratio of 4:2 reaches the best balance and the battery expansion is also minimal, proving that the flexible skeleton and the composite SEI effectively inhibit the expansion of the silicon-based negative electrode under the synergistic effect, and the positive and negative electrodes form a stable interface with the electrolyte, thereby obtaining better electrochemical performance.

[0078] In addition, it can be seen from Table 1 that when an unsaturated cyanoacrylic acid monomer without phenyl group is used, the flexibility of the entire polymer chain segment deteriorates, which will lead to more obvious expansion of the negative electrode and poor battery cycle performance.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite polymer solid electrolyte, characterized in that: The invention comprises a fluoroacrylate monomer, an unsaturated cyanophenyl acrylic acid monomer, a functional additive, a lithium salt and an initiator.

2. The composite polymer solid electrolyte according to claim 1, characterized in that: The molar ratio of the fluoroacrylate monomer to the unsaturated cyanophenyl acrylic acid monomer is 4:1 to 4:

6.

3. The composite polymer solid electrolyte according to claim 2, characterized in that: The fluoroacrylate monomer is at least one of 2-fluoroethyl acrylate, perfluoroalkyl acrylate, perfluoropolyether (meth) acrylate, perfluorooctylpropyl acrylate, trifluoroethyl acrylate and perfluoroalkylethyl acrylate; The unsaturated cyanophenyl acrylic acid monomer is at least one of ethyl 2-(4-cyanophenyl)acrylate, 3-(2-cyanophenyl)acrylate, tert-butyl 3-(4-cyanophenyl)acrylate, methyl 3-(3-benzonitrile)acrylate and ethyl 4-cyanocinnamate.

4. The composite polymer solid electrolyte according to claim 3, characterized in that: The ratio of the mass of the functional additive to the mass of the fluoroacrylate monomer and the unsaturated cyanophenyl acrylic acid monomer is 10:1 to 25:1; The molar concentration of the lithium salt in the mixture of the fluoroacrylate monomer, the unsaturated cyanophenyl acrylic acid monomer and the functional additive is 0.8 to 2 mol / L; The mass of the initiator is 0.2-5 wt % of the total mass of the fluoroacrylate monomer and the unsaturated cyanophenyl acrylic acid monomer.

5. The composite polymer solid electrolyte according to claim 4, characterized in that: The functional additive is at least one of vinylene carbonate, fluoroethylene carbonate, vinyl carbonate, (trimethylsilyl) phosphite, tris(trimethylsilyl) borate, 1,3-propane sultone, vinyl sulfate, methylene disulfonate, succinonitrile, adiponitrile, ethylene glycol dimethyl ether and dimethyl carbonate; The lithium salt is at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium tetrafluoroborate; The initiator is at least one of azobisisobutyronitrile, dibenzamide peroxide, benzoyl peroxyacetic acid and dibutyl peroxybenzoylformate.

6. A solid-state battery, characterized in that: The invention comprises a positive electrode, a negative electrode, a separator and the composite polymer solid electrolyte according to any one of claims 1 to 5, wherein the composite polymer solid electrolyte is in contact with both the positive electrode and the negative electrode.

7. The solid-state battery according to claim 6, characterized in that: The positive electrode is a high-nickel ternary positive electrode, and the negative electrode is a silicon-based negative electrode.

8. A method for preparing a solid-state battery according to claim 6 or 7, characterized in that: The following steps are involved: Step 1, firstly, mixing a fluoroacrylate monomer and an unsaturated cyanophenyl acrylic acid monomer, then adding a functional additive and continuing to mix evenly, then adding a lithium salt and mixing evenly, and finally adding an initiator and mixing evenly to obtain a composite polymer solid electrolyte precursor; Step 2: First assemble the positive and negative electrodes and the separator, then inject the composite polymer solid electrolyte precursor, and then sequentially perform standing, pressurizing and thermal curing to obtain a solid-state battery.

9. The preparation method according to claim 8, characterized in that: The standing temperature is room temperature, and the standing time is 12 to 48 hours.

10. The preparation method according to claim 8, characterized in that: The thermal curing temperature is 50 to 90°C and the time is 2 to 12 hours; The pressurization pressure is 0.2-1 MPa, and the time is 30-120 seconds.